องค์กรพิเศษเฉพาะกิจเพื่อตรวจสอบการทุจริตที่จัดตั้งขึ้นภายหลังการเปลี่ยนแปลงทางการเมือง - จาริณี ลิขิตธรรมวาณิช (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This Thesis has its objective to study and analyze special task force organization for corruption inspection established after major political change of Thailand. It studied the law that established the bodies and the verdicts of the court relating to them whether those followed the rule of law that is intended to hold justice between the person under inspection and the result of the inspection that hold the nation’s best interests The study shows the establishment of organization or ad hoc legal person following a major political change is to inspect corrupted practice of persons who were in the dissolved government and forfeit their assets and related persons’ assets. The law enacted shall support the establishment of the organization or special legal person under special power of a Prime Minister or coup d etat body. Each occasion this organization or special legal person may be entrusted with both executive power and legislative power, depending on respective law. Procedure for inspection begins with drawing specialists from public organizations to be committee members. The court had judgment for the first two cases in the way that limits its own power, while the last two cases followed the law governing the case. Development of the law that gives power to the special task force organization or legal person leaves the issue to examine legal status and exploitation of their power. The process could not guarantee justice for the examinees nor transparency and un-biasness. The aim could be to eliminate political opponents who were in the previous government. It could also not guarantee the jurisdiction’s best interest. Because the result came from the use of non-democratic power or the coup d’etat body.